Public Health Midwives’ role in health education regarding vaginal discharge: A Cross Sectional Descriptive Study (International Journal of Scientific Research and Management (IJSRM), 2016)
Objectives: Public Health Midwife (PHM) is the key health care provider at the domiciliary level in Sri Lankan health care system. They indulge in maternal and childcare services in the Sri Lankan community setting. This study was carried out to assess knowledge and attitudes towards health education activities of the PHMs related to vaginal discharge. Study Design: Community based cross sectional study. Methods: A self-developed, validated, pretested self-administered questionnaire was used to gather data from PHMs who are serving to a socially marginalized community in the Colombo District in the Western Province of Sri Lanka. Results: A total of 56 PHMs participated with a response rate of 82%. Mean age was 36.57 years (SD±10.10). Mean duration of working was 9.05years (SD±9.07). Mean knowledge score was 53.7 (SD ± 12.36). Reproductive tract infections and causes for pathological vaginal discharge were found as poor knowledge areas. Majority (n=29, 91.1%) agreed that they discuss women’s health issues and educate them regarding prevention of diseases (n=52, 92.9%). lack of available time (n=46, 82.1%), lack of teaching materials (n=44, 78.6%), lack of a good educational environment (n=45, 80.4%) and lack of knowledge (n=38, 67.9%) and women’s lack of interest in learning (n= 46, 82.1%) were identified as the main challenges for health education. Conclusions: The findings suggest that majority of PHMs have only a moderate level of knowledge regarding vaginal discharge and there is a need for continuing education in order to improve confidence in health education for women’s health issues.